2005
DOI: 10.1080/09546630510011801
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of topical caffeine in the treatment of psoriasis vulgaris

Abstract: Based on the results of the trial, topical caffeine is an effective, safe and inexpensive treatment for psoriasis, with a delay in action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Micellar paclitaxel significantly improved psoriasis in a prospective phase II study [53]. A study reported significant effectiveness of topical caffeine [54]. “Calcium channel blocker” nifedipine is found to be inductor of the disease in a case control study [55].…”
Section: Resultsmentioning
confidence: 98%
“…Micellar paclitaxel significantly improved psoriasis in a prospective phase II study [53]. A study reported significant effectiveness of topical caffeine [54]. “Calcium channel blocker” nifedipine is found to be inductor of the disease in a case control study [55].…”
Section: Resultsmentioning
confidence: 98%
“…In psoriasis patients, serum as well as epidermis, adenosine deaminase levels were significantly elevated (Bü kü lmez et al, 2000) and may reflect the accelerated salvage pathways of nucleic acid metabolism associated with the hyperproliferative epidermis (Koizumi et al, 1983). Based on the results of a trial, it was concluded that caffeine, a P1 adenosine receptor antagonist, ''is an effective, safe and inexpensive treatment for psoriasis'' (Vali et al, 2005), as in psoriatic epidermis, the level of cAMP decreases and caffeine increases concentrations of intracellular cAMP.…”
Section: Skin Pathology Psoriasismentioning
confidence: 97%
“…Caffeine has been proposed as a potential treatment for dermatological conditions such as psoriasis [135], viral infections [136,137] and cellulite treatment [138,139]. Iontophoresis has also demonstrated the ability to enhance the epidermal delivery of macromolecules (up to 10 kDa) [140].…”
Section: Iontophoresismentioning
confidence: 99%